The effects of resilience and basic personality traits on subjective well-being in elderly - Petrović, Jelica; Kovač, Lila; Dinić, Bojana M. (Primenjena psihologija, 2024)
The aim of this research was to examine the prediction of aspects of subjective well-being based on resilience and seven basic personality traits in users of gerontological centers, and the incremental contribution of basic personality traits in explaining adaptation to old age, beyond the variance explained by resilience. The sample consisted of 151 participants (54.3% female) with an average age of 80 years. Satisfaction with life, as cognitive indicator, and emotional distress (anxiety, depression, and stress) were used as indicators of subjective well-being. The results showed that resilience, neuroticism (in the negative direction) and positive valence predicted life satisfaction in the elderly. In predicting emotional distress, neuroticism stood out as a key predictor, while the significant contribution of resilience is dimnished by introducing personality traits into the model. The results provide a more complete picture of the relationships between resilience, personality traiits, and subjective well-being in a sample of the elderly in Serbia, and confirm the importance of studying these relationships from a developmental perspective.